Perancangan Sistem Informasi Monitoring Perkembangan Anak Usia Dini Berbasis Web Pada Yayasan Harapan Ibu RA. Insan Harapan - Putria, Narti Eka; Hakim, Arif Rahman; Yulia, Yulia (AI Society & STMIK Indonesia, 2024)
Early childhood education foundation Yayasan Harapan Ibu RA. Insan Harapan was established in 2016. Yayasan Harapan Ibu RA. Insan Harapan still utilizes information technology to support various activities including having a WhatsApp group. Most schools still do manual monitoring, the form of reporting using supporting books. Manual recording of reports can also cause human error or errors caused by humans such as errors in filling in data or losing data files so that monitoring between guardians and homeroom teachers is not in harmony. The purpose of this study is to design a web-based early childhood development monitoring information system, to make it easier for guardians and teachers to have harmony in monitoring child development and to facilitate school academic activities. The method used is the SDLC (System Development Life Cycle) method, PHP is used to develop the website, and MySQL as a database server. The design of a web-based student monitoring information system helps schools provide information on academic activities of child development to parents/guardians online, and makes it easier for schools to input student data, teacher data, grade data, class data, report creation, data updates, new student registration, and promotions.